Т.ҚАЙЫПБЕРГЕНОВ ПОВЕСТЛЕРИНДЕ КӨРКЕМ ДЕТАЛДЫӉ ХЫЗМЕТИ («Уйқысыз түнлер», «Тәнҳә өзиңе мәлим сыр» повестлери мысалында) - Сәрсенбаев, Қ.Ж. (FAN va JAMIYAT, 2023)
The article discusses the writer’s skillful use of artistic details and motifs in the works. The essence of the details was taken into account while revealing the character of the writer.